Depression and substance use: The CES-D's utility in predicting treatment outcomes in a longitudinal multi-site study of residential treatment centers. (March 2021) - Morris, Nicole M.; Fulton, Joe A.; Youngren, Westley A; Schumacher, John R.; Ingram, Paul B.
Highlights: The CES-D is a clinically useful screening measure. Residential substance use has three groups of depressive symptoms. Group membership predicts severity and rate of change for depression. Group membership also predicts treatment discharge status. Abstract: This investigation utilized a large sample of individuals undergoing substance use treatment to examine the CES-D's structural validity and establish its predictive utility relative to treatment discharge. The sample included 5750 individuals who were receiving substance abuse treatment at 19 different residential treatment facilities. The CES-D was administered to participants over the course of their time in a residential inpatient substance use treatment program. The present study used a split sample method to conduct both exploratory (EFA) and confirmatory (CFA) factor analyses. Results of both the EFA and CFA indicated that the CES-D contains three first order factors measuring negative mood, positive affect, and interpersonal interactions as well as a second-order high score factor which can be used to guide interpretation and symptom monitoring. Individuals receiving residential treatment fell into one of three distinct groups based on their CES-D scores, and that their scores (and subsequent trajectories of scores over time) were differentially related to discharge status. Implications for practice and the utility of the CES-D within substance use populations are discussed.